A dissimilar biosimilar? Lichenoid drug eruption induced by an infliximab biosimilar. (1st April 2018) - Gonzalez, N.; Patel, P.; Han, G.
Summary: The advent of therapeutic antibodies, or biological medications, has transformed the treatment of many inflammatory diseases in dermatology. Recently, the development of biosimilars, biological drugs that are highly similar in quality, safety and efficacy to approved biologics, has changed this landscape. Although biosimilars are not identical to their reference product, they are required to have the same mechanism of action, route of administration, dosage form and strength as the reference product. This also leads to the possibility that subtle differences in the activity of these biosimilars can lead to differing clinical responses. We report the first case of a lichenoid eruption induced by a biosimilar to infliximab after switching from infliximab. Several days after initial infusion of the biosimilar, the patient developed a pruritic papulosquamous eruption that was biopsied to reveal a lichenoid drug eruption. Possible mechanisms for lichenoid drug eruptions as a result of tumour necrosis factor‐α inhibitor administration are discussed, along with reasons why such a reaction may occur with a biosimilar but not the original, reference product. This case report calls attention to the unique differences between biosimilars and biological medications that a clinician should consider prior to prescribing these medications.